SOLE Cooperative Learning Model: Its Effect On Students’ Learning Autonomy In Islamic Religious Education - Anggi Ismiyanti; Chairul Anwar; Sunarto Sunarto (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to analyze the effect of the Self-Organized Learning Environment (SOLE) learning model on students’ learning autonomy in Islamic Religious Education (IRE). The study is motivated by the low level of students’ learning autonomy, particularly in terms of discipline and initiative. However, previous studies on the implementation of SOLE have predominantly focused on general subjects such as mathematics and science, while studies within the context of Islamic Religious Education remain limited. Therefore, this study offers novelty by examining the effectiveness of SOLE in enhancing learning autonomy in IRE. The method used in this study is a quasi-experimental design with a post-test only control group design, involving eighth-grade students as the research subjects. Data were collected using a learning autonomy questionnaire that had been tested for validity and reliability, and were analyzed using normality, homogeneity, and Mann–Whitney tests. The results show that the Mann–Whitney test produced a significance value of 0.000 (p < 0.05) with a Z value of –3.806, indicating a significant difference between the experimental and control groups. The implementation of the SOLE model has been proven to significantly improve students’ learning autonomy, particularly in the aspect of initiative. Students became more active in seeking information, more confident in making decisions, and more capable of managing time and solving problems independently. This study contributes to the expansion of SOLE implementation in Islamic Religious Education, which integrates cognitive, affective, and psychomotor domains. The findings also confirm that SOLE is an effective 21st-century learning strategy that supports digital literacy, critical thinking, and students’ learning autonomy.